A taxonomic revision of the genus Mesophleps Hübner, 1825 (Lepidoptera: Gelechiidae) - Li, Houhun; Sattler, Klaus (Zootaxa, 2012)
The genus Mesophleps Hübner (Lepidoptera: Gelechiidae) is revised; 54 available names (including one unjustifiedemendation), one junior primary homonym and one unavailable name were considered; type material of 44 previouslydescribed nominal species was examined. Nine new species are described: M. acutunca sp. nov., M. bifidella sp. nov., M.unguella sp. nov., M. gigantella sp. nov., M. coffeae sp. nov., M. parvella sp. nov., M. aspina sp. nov., M. truncatella sp.nov. and M. undulatella sp. nov. Two possibly new species are discussed but not formally named for lack of material.Twenty-five new combinations are introduced: M. safranella (Legrand, 1965) comb. nov., M. epichorda (Turner, 1919)comb. nov., M. tabellata (Meyrick, 1913) comb. nov., M. crocina (Meyrick, 1904) comb. nov., M. ochracella (Turati,1926) comb. nov., M. geodes (Meyrick, 1929) comb. nov., M. catericta (Meyrick, 1927) comb. nov., M. tephrastis(Meyrick, 1904) comb. nov., M. cycnobathra (Lower, 1898) comb. nov., M. tetrachroa (Lower, 1898) comb. nov., M.ochroloma (Lower, 1901) comb. nov., M. trichombra (Lower, 1898) comb. nov., M. mylicotis (Meyrick, 1904) comb. nov.,M. macrosemus (Lower, 1900) comb. nov., M. apentheta (Turner, 1919) comb. nov., M. meliphanes (Lower, 1894) comb.nov., M. chloranthes (Lower, 1900) comb. nov., M. centrothetis (Meyrick, 1904) comb. nov., M. chloristis (Meyrick,1904) comb. nov., M. argonota (Lower, 1901) comb. nov., Megacraspedus arnaldi (Turati & Krüger, 1936) comb. nov.,Aponoea cinerellus (Turati, 1930) comb. nov., Pycnobathra acromelas (Turner, 1919) comb. nov., Sarotorna mesoleuca(Lower, 1900) comb. nov., S. dentata Meyrick, 1904, comb. nov. One species, Nothris mesophracta Turner, 1919, isremoved from Mesophleps but no current genus is available. Fourteen new synonymies (one genus, 13 species-group taxa)are established: Bucolarcha Meyrick, 1929, syn. nov. of Mesophleps Hübner, [1825]; Stiphrostola longinqua Meyrick,1923, syn. nov. and Brachyacma trychota Meyrick, 1929, syn. nov. of M. ioloncha (Meyrick, 1905); Lipatia crotalariellaBusck, 1910, syn. nov. of M. adustipennis (Walsingham, 1897); Brachyacma epichorda Turner, 1919, syn. nov. of M.epiochra (Meyrick, 1886); Mesophleps pudicellus var. apicellus Caradja, 1920, syn. nov. and Mesophleps silacellus subsp.calaritanus Amsel, 1939, syn. nov. of M. silacella (Hübner, 1796); Mesophleps lala Agenjo, [1961], syn. nov. of M.corsicella (Herrich-Schäffer, 1856); Crossobela barysphena Meyrick, 1923, syn. nov. of M. trinotella Herrich-Schäffer,1856; Mesophleps orientella Nel & Nel, 2003, syn. n. and Mesophleps gallicella Varenne & Nel, 2011, syn. nov. of M.ochracella (Turati, 1926); Nothris centrothetis Meyrick, 1904, syn. nov. and Nothris chloristis Meyrick, 1904, syn. nov.of M. chloranthes (Lower, 1900); Mesophleps cinerellus Turati, 1930, syn. nov. of Aponoea obtusipalpis Walsingham,1905. One genus and one species are recalled from synonymy: Pycnobathra Lower, 1901, gen. rev., and M. ioloncha(Meyrick, 1905) sp. rev. Lectotypes are designated, in accordance with the Code, article 74.7.3, for 14 species: Gelechiapalpigera Walsingham, 1891; Paraspistes ioloncha Meyrick, 1905; Lathontogenus adustipennis Walsingham, 1897;Brachyacma epichorda Turner, 1919; Nothris crocina Meyrick, 1904; Nothris ochracella Turati, 1926; Nothris tephrastisMeyrick, 1904; Ypsolophus ochroloma Lower, 1901; Ypsolophus macrosemus Lower, 1900; Nothris centrothetis Meyrick,1904; Nothris chloristis Meyrick, 1904; Ypsolophus argonota Lower, 1901; Mesophleps arnaldi Turati & Krüger, 1936,and Mesophleps cinerellus Turati, 1930. Mesophleps is a widely distributed Old World genus, except for one New Worldspecies, with seed-feeding larvae on Cupressaceae, Cistaceae, Cruciferae (Brassicaceae), Leguminosae (Fabaceae), Rubiaceae and doubtfully Dipterocarpaceae.